2018
DOI: 10.1364/boe.9.001783
|View full text |Cite
|
Sign up to set email alerts
|

Technique of laser chromosome welding for chromosome repair and artificial chromosome creation

Abstract: Abstract:Here we report a technique of laser chromosome welding that uses a violet pulse laser micro-beam for welding. The technique can integrate any size of a desired chromosome fragment into recipient chromosomes by combining with other techniques of laser chromosome manipulation such as chromosome cutting, moving, and stretching. We demonstrated that our method could perform chromosomal modifications with high precision, speed and ease of use in the absence of restriction enzymes, DNA ligases and DNA polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Since we first described the use of a laser scissors system in combination with a tweezers (Liang et al, 1993), very few studies using the two optical modalities combined have been conducted. However, one study used a pulsed violet laser scissors to cut chromosomes into small pieces and then used laser tweezers to move the cut piece to another chromosome where it was fused to create a chromosome with the added fragment (Huang et al, 2018). The authors suggested that this method ".…”
Section: Tweezers and Scissorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we first described the use of a laser scissors system in combination with a tweezers (Liang et al, 1993), very few studies using the two optical modalities combined have been conducted. However, one study used a pulsed violet laser scissors to cut chromosomes into small pieces and then used laser tweezers to move the cut piece to another chromosome where it was fused to create a chromosome with the added fragment (Huang et al, 2018). The authors suggested that this method ".…”
Section: Tweezers and Scissorsmentioning
confidence: 99%
“…(7) Laser microdissection of chromosome regions coupled with PCR analysis has been developed as a precise optical tool for genetic studies of Huntington’s disease ( Hadano et al, 1991 ) and other gene sites on human chromosomes ( He et al, 1997 ). In one recent study, a laser tweezers was used to move laser cut chromosome fragments inside the live cell to “weld” together new combinations of chromosomes ( Huang et al, 2018 ). The above studies used a variety of lasers and optical systems and led to the development of a combined laser scissor and tweezers microscope that could be accessed through the internet using the LAMP Robolase control panel, making the technology available on a global scale, as in Figures 8 , 9 (modified after Botvinick and Berns, 2005 ).…”
Section: Tweezersmentioning
confidence: 99%
“…The second example, more recent, is quite relevant in the field of genetic manipulation, as it reports on the successful welding of two chromosomes fragments into a single genetic unit (Huang et al, 2018). The chosen biological model were polytene chromosomes of D. melanogaster, particularly fitted for manipulation because of their large size.…”
Section: Chromosome Manipulationmentioning
confidence: 99%
“…Given the role of telomeres in processes such as aging, genome preservation/instability and cancer, the LS-OT manipulation of telomeres should be a particularly intense research area. Additionally, the recently reported possibility to conduct chromosomal welding represents an excellent proxy for a plethora of chromosomal structural mutations and fusion chromosomes (Huang et al, 2018).…”
Section: Chromatin and Chromosomes Lesionsmentioning
confidence: 99%
See 1 more Smart Citation